The effects of quality certification in establishing and developing customer - supplier relationships - Milošević, Isidora Miloje; Trajković, Ana; Rajić, Tamara; Nikolić, Đorđe; Arsić, Sanela (Serbian Journal of Management, 2018)
Customer-supplier relationship is extremely important for the success of the company which implies that it is necessary to maximize trust and cooperation when setting and achieving company goals. This study represents an analysis of customer –supplier relationship from the aspect of both “certified” and “non-certified” companies in Serbia. Although the number of non-certified companies in Serbia is much higher than the number of certified ones, companies that have showed interest in taking part in this research are those that have certified quality management system, even though they represent only 2.11% of the total number of companies in Serbia. The data collected in this study were analyzed in structural equation model (SEM), in which the multi-group confirmatory factor analysis (MGCFA) was used in order to perform comparative measurements using two samples from different companies- both “certified” and “non-certified” ones.